2016
DOI: 10.1002/jemt.22638
|View full text |Cite
|
Sign up to set email alerts
|

Development and morphological changes in the vaginal closure membrane throughout gestation inGalea spixii(Rodentia: Caviidae)

Abstract: Present research was carried out in order to perform the monitoring of development, recognizes the type of tissue and describes histological and cellular changes of the vaginal closure membrane (VCM) throughout pregnancy in Galea spixii. The results showed that at 20 days of gestation (DG), the VCM occludes completely the external vaginal ostium. Microscopically, the VCM presented juxtaposed cells, derived from the stratum germinative of the stratified epithelium of vaginal mucosa at 20 DG and areas with cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Further studies are needed to elucidate the factors involved in the formation process of the mucus plug and vaginal closure membrane. Until now, Santos, Oliveira, et al () demonstrated that the vaginal closure membrane has a cellular formation and breakage control in pregnant G. spixii ; its formation is associated with the proliferation of cells in the germinative layer of the epithelium, with the formation of desmosome junctions between these cells and their rupture being associated with apoptosis and loss of cell adhesion. Notably, the formation of this mucus plug and the consequent formation of this closure membrane is a typical characteristic of rodents, and it could be associated with preventing the action of males after copulation (Adrian & Sachser, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies are needed to elucidate the factors involved in the formation process of the mucus plug and vaginal closure membrane. Until now, Santos, Oliveira, et al () demonstrated that the vaginal closure membrane has a cellular formation and breakage control in pregnant G. spixii ; its formation is associated with the proliferation of cells in the germinative layer of the epithelium, with the formation of desmosome junctions between these cells and their rupture being associated with apoptosis and loss of cell adhesion. Notably, the formation of this mucus plug and the consequent formation of this closure membrane is a typical characteristic of rodents, and it could be associated with preventing the action of males after copulation (Adrian & Sachser, ).…”
Section: Discussionmentioning
confidence: 99%
“…The reproductive system of these animals consists of ovaries, uterine tubes, a partially double uterus, cervix, and vagina (Martins et al, ; Mayor, Bodmer, & Bejar, ; Singh, Adogwa, Mollineau, & Garcia, ). Similar to other rodent species (e.g., Cavia porcellus (Stockard & Papanicolaou, ), Thryonomys swinderianus (Addo et al, ), Octodon degus (Mahoney, Rossi, Hagenauer, & Lee, ), and Galea spixii (Santos et al, , )), a vaginal closure membrane forms in agoutis at certain stages of the estrous cycle (Weir, ).…”
Section: Introductionmentioning
confidence: 93%
“…Current analysis detailed the morphological development of the adrenal glands of SYT cavies from the embryo phase to puberty. Data are important since SYT cavies have been used as experimental models for embryonic studies [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] , studies on reproduction physiology [5][6][7][8][9][10][11][12][13][14][15][16] and on the morphology and adrenal steroidogenesis in adult animals [4] . Current analysis revealed topographic asymmetry between the adrenal glands, or rather, the right gland lying cranially towards the left.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the species is bred in captivity for sustenance. Moreover, due peculiar morphological and reproductive characteristics found in previous studies, SYT cavies serve as an experimental model for research on reproductive biology (Oliveira et al, ; Santos et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Female Spix's yellow‐toothed cavies have a continuous poliestral cycle (Oliveira et al, ) that lasts 14–19 days in captive females. A vaginal closure membrane develops during the estrous cycle (Santos et al, ) and pregnancy (Santos et al, ), and different steroidogenic enzymes are present in the vaginal epithelium at different cycle phases corresponding with epithelial proliferation (Santos et al, ). With regard to cellular proliferation on the vaginal epithelium, one study (Deanesly, ) described the vaginal epithelium of Cavia porcellus is variously stimulated by different hormones resulting from ovarian follicular development throughout the estrous cycle.…”
Section: Introductionmentioning
confidence: 99%